Laser-induced breakdown spectroscopy as a reliable analytical method for classifying commercial cheese samples based on their cooking/stretching process. (1st October 2022) - Sezer, Banu; Ozturk, Mustafa; Ayvaz, Huseyin; Apaydın, Hakan; Boyaci, Ismail Hakkı
Highlights: A new LIBS method was proposed to discriminate the Kashar and processed cheese samples. PLS-DA and PCA models are used to discriminate the samples based on elemental content. The developed method with favorable sensitivity and selectivity is easy to implement with high predictive ability. High-precision quantification of elemental content of cheese samples. Abstract: The present work evaluates the possibility of using laser-induced breakdown spectroscopy (LIBS) coupled with chemometric methods to classify cheese samples (namely Kashar cheese and processed cheese) based on their cooking/stretching process. Chemometric analysis of the data provided by LIBS and ICP-OES/AAS analyses made it possible to discriminate between the two cheese types regarding their elemental profiles. The principal component analysis model was able to discriminate the Kashar cheese with an explained variance of 97.02%. Furthermore, the partial least squares discriminant analysis model perfectly classified the Kashar samples with a prediction ability of 100%. Furthermore, calibration and validation models for Mg, Ca, Na, P, Zn, and K elements for both Kashar and processed cheese samples were developed using partial least square regression yielding high correlation coefficients and low root mean square errors. Overall, this study indicates that LIBS with chemometrics can be an easy-to-use and rapid monitoring system for cheese classification.